Chapter Il protoslavo, l'etnogenesi slava e il contatto linguistico. Problemi e prospettive di ricerca - CALDARELLI, Raffaele (Biblioteca di Studi Slavistici, 2018)
Reconstructed Proto-Slavic represents Slavic linguistic situation about 600 A. D. This form of Slavic language became one of the pillars of the Slavic ethnogenesis, which was also the result of social and political factors, including Byzantine initiative.About earlier ethnogenetic processes we know very little: probably there were no large phenomena of linguistic mixture, rather there were phenomena of linguistic shift to Slavic, in particular of Finnic peoples, with cultural (not linguistic) substratum traces of their past.